Effect of laser remelting of plasma sprayed coating of Cr-Ni-Re. Issue 1 (May 2021) - Śliwński, P; Węglowski, M S; Dworak, J; Dymek, S; Kalemba-Rec, I; Wrona, A; Kustra, K; Lis, M
Abstract: Atmospheric plasma spraying (APS) consists in injecting a powder feedstock material in a plasma jet to melt and accelerate the injected particles and spray them onto a substrate. However, this mechanism of coating formation induces the presence of pores and micro-cracks. In order to eliminate those defects, laser remleting may be used to improve the properties and performances of plasma sprayed coatings. In the present paper, the Ni-Cr-Re coatings fabricated by plasma spraying on stainless steel substrate were remelted by CO2 laser, and the effects of laser remelting were studied. The structure and chemical composition of plasma sprayed and laser remelted coatings were analyzed using scanning electron microscopy (SEM) and energy disperse spectroscopy (EDS). The results show that the laser remelted coating becomes much denser and, moreover, the chemical composition of the coatings becomes homogeneous.